Vertex degree distributions of growing graphs: calculation methods using error control - V. N. Zadorozhnyi; E. B. Yudin; V. A. Badryzlov (Омский научный вестник)
Methods for calculating final distributions of vertex degrees in growing graphs with a nonlinear rule of preferred binding are developed. The problem of calculation errors control is solved. Formulas for determining the key properties of calculated distributions are developed. Examples of calculation with error control are given.